Assessment of genetic and epigenetic changes during cell culture ageing and relations with somaclonal variation in Coffea arabica - Bobadilla Landey, R.; Cenci, A.; Guyot, R.; Bertrand, B.; Georget, F.; Dechamp, E.; Herrera, J.C.; Aribi, J.; Lashermes, P.; Etienne, H. (Springer, 2015)
Long-term cell cultures were used in coffee to study the cytological, genetic and epigenetic changes occurring during cell culture ageing. The objective was to identify the mechanisms associated with somaclonal variation (SV). Three embryogenic cell lines were established in Coffea arabica (2n = 4x = 44) and somatic seedlings were regenerated after 4, 11 and 27 months. Phenotyping and AFLP, MSAP, SSAP molecular markers were performed on 199 and 124 plants, respectively. SV were only observed from the 11 and 27-month-old cultures, affecting 30 and 94 % of regenerated plants, respectively. Chromosome counts performed on 15 plants showed that normal plants systematically displayed normal chromosome numbers and that, conversely, aneuploidy (monosomy) was systematically found in variants. The allopolyploid structure of C. arabica allowed aneuploid cells to survive and regenerate viable plants. No polymorphic fragments were observed between the AFLP and SSAP electrophoretic profiles of mother plants and those of the in vitro progeny. Methylation polymorphism was low and ranged between 0.087 and 0.149 % irrespective of the culture age. The number of methylation changes per plant—normal or variant—was limited and ranged from 0 (55–80 % of the plants) to 4. The three cell lines showed similar SV rate increases during cell culture ageing and produced plants with similar molecular patterns indicating a non random process. The results showed that cell culture ageing is highly mutagenic in coffee and chromosomal rearrangements are directly linked to SV. Conversely, the analysis of methylation and transposable elements changes did not reveal any relation between the epigenetic patterns and SV.